2017
DOI: 10.1364/ao.56.003077
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinearity characterization of array spectroradiometers for the solar UV measurements

Abstract: Array spectroradiometers are attractive alternatives to scanning spectroradiometers in solar ultraviolet measurements. However, the measurement of solar spectral irradiance imposes stringent requirements for the linearity of the instruments. In this article, two array spectroradiometers were characterized for nonlinearity. Significant nonlinearities, in excess of 10%, as a function of analog-to-digital converter counts were discovered. Additional nonlinearities as a function of integration time were observed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 18 publications
0
7
0
1
Order By: Relevance
“…The linearity of the BTS2048-UV-S was tested using both the integration time and the irradiance variation methods (Pulli et al 2017). For the integration time method, the spectral irradiance of the incident radiation is kept constant while the instrument's integration time is varied over a wide range.…”
Section: Characterisationmentioning
confidence: 99%
“…The linearity of the BTS2048-UV-S was tested using both the integration time and the irradiance variation methods (Pulli et al 2017). For the integration time method, the spectral irradiance of the incident radiation is kept constant while the instrument's integration time is varied over a wide range.…”
Section: Characterisationmentioning
confidence: 99%
“…The nonlinearity of an array spectroradiometer depends for instance on the used detector chip, the readout electronics (analog-to-digital converter (ADC)) and the remaining deviation after applying a correction based on a characterisation of the detector system (Pulli et al 2017). Since the electronics, detector chip and characterisation procedure are identical to the UV-BTS, Figure 1.…”
Section: Vis-btsmentioning
confidence: 99%
“…Experiments have indicated that the non-linearity at an intensity of about 50,000 (of a maximum of 65,535) counts is in the range of up to 1000 counts on the intensity scale, or up to 0.04 absorption units on the absorbance scale, using a Hamamatsu C10082CA mini-spectrometer [4]. Non-linearities in the light intensity response of CCD spectrometers greater than 10% were found in recent studies and the corresponding corrections resulted a non-linearity of less than 0.5% [5,6]; in one study a custom-designed spectrometer [5] was used and in the other an Avantes Avaspec-ULS2048L spectrometer and a StellarNet Blue-Wave spectrometer [6] were used. To the best of our knowledge, Ocean Optics Inc. is the only supplier that provides non-linearity correction software (OOINLCorrect, Ocean Optics Inc., Dunedin, FA, USA) for their CCD spectrometers, which provides linearities >99.8% [7].…”
Section: Introductionmentioning
confidence: 99%